Product Cordial and Total Product Cordial Labelings of Pn+1m. (5th January 2015) - Gao, Zhen-Bin; Sun, Guang-Yi; Zhang, Yuan-Ning; Meng, Yu; Lau, Gee-Choon
Abstract : We proved that P n + 1 m is total product cordial. We also give sufficient conditions for the graph to admit (or not admit) a product cordial labeling.